2018
DOI: 10.1002/acm2.12482
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative variations in texture analysis features dependent on MRI scanning parameters: A phantom model

Abstract: ObjectivesTo evaluate the influence of MRI scanning parameters on texture analysis features.MethodsPublicly available data from the Reference Image Database to Evaluate Therapy Response (RIDER) project sponsored by The Cancer Imaging Archive included MRIs on a phantom comprised of 18 25‐mm doped, gel‐filled tubes, and 1 20‐mm tube containing 0.25 mM Gd‐DTPA (EuroSpinII Test Object5, Diagnostic Sonar, Ltd, West Lothian, Scotland). MRIs performed on a 1.5 T GE HD, 1.5 T Siemens Espree (VB13), or 3.0 T GE HD with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
49
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 40 publications
2
49
0
Order By: Relevance
“…Magnetic resonance images undergo of some intrinsic acquisition artifacts, and different scanners with various acquisition parameters, and protocols, severely impeded the multicenter applicability of MRI‐based radiomics, the image preprocessing takes an essential part in the facilitating quantification analysis and make more repeatable and comparable results. However, the lack of pre‐specific image standardization methods in the mMRI‐based radiomics analysis may also affect the reproducibility and reliability of the features.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic resonance images undergo of some intrinsic acquisition artifacts, and different scanners with various acquisition parameters, and protocols, severely impeded the multicenter applicability of MRI‐based radiomics, the image preprocessing takes an essential part in the facilitating quantification analysis and make more repeatable and comparable results. However, the lack of pre‐specific image standardization methods in the mMRI‐based radiomics analysis may also affect the reproducibility and reliability of the features.…”
Section: Discussionmentioning
confidence: 99%
“…Given that MRI undergoes of various inherent acquisition artifacts and noises such as lack of standard intensity for inter‐ and intra‐scanner variability even for the same protocol, body region, and patient; intensity non‐uniformity as a result of reduced radio frequency, coil uniformity, nonlinear fields, gradient field, magnetic field, and etc. ; image preprocessing method suchlike intensity normalization, bias field correction, and noise smoothing can facilitate quantitative MRI analysis and make the radiomics results more repeatable and comparable . Currently, many attentions of the GBM mMRI‐based radiomics studies were drowned to prognosis and prediction model, while they have not used a pre‐specific image preprocessing pipeline.…”
Section: Introductionmentioning
confidence: 99%
“…Each component of the workflow is important, and a lack of standardization limits reproducibility . For example, it has been shown that variations in image acquisition and reconstruction parameters lead to inconsistent findings between different datasets . An additional obstacle is the lack of standardization for segmentation, as it may be performed manually, automatically, or semiautomatically.…”
mentioning
confidence: 99%
“…Pooling data from different centers is necessary, but it runs the risk of introducing bias to the values of texture features. Indeed, each step of the radiomics process can introduce variability independently from the intrinsic heterogeneity of the tumor; for instance: MRI field strength, manufacturers, coils, acquisition parameters, segmentation, voxel‐size resampling, normalization techniques, or gray‐level discretization . Previous studies have demonstrated that temporal parameters (ie, scan duration and temporal resolution) could significantly modify the ability to discriminate benign from malignant prostate or breast lesions, but they were based on average values of DCE‐MRI indices or morphology of the time–intensity curves.…”
mentioning
confidence: 99%
“…Indeed, each step of the radiomics process can introduce variability independently from the intrinsic heterogeneity of the tumor; for instance: MRI field strength, manufacturers, coils, acquisition parameters, segmentation, voxel-size resampling, normalization techniques, or gray-level discretization. [20][21][22][23] Previous studies have demonstrated that temporal parameters (ie, scan duration and temporal resolution) could significantly modify the ability to discriminate benign from malignant prostate or breast lesions, [24][25][26] but they were based on average values of DCE-MRI indices or morphology of the time-intensity curves. Only one study has focused on the stability of texture features extracted from computed tomography (CT) perfusion maps identifying an influence of temporal resolution.…”
mentioning
confidence: 99%